Our responsibilities for future generations from a social-emotional learning perspective: revisiting mindfulness - Konishi, Chiaki; Chowdhury, Farhin; Tesolin, Julia; Strouf, Kendra (Frontiers in Education, 2024)
This article provides the readers with an opportunity to revisit the original purpose of mindfulness and to learn about some concerns and challenges raised in current understandings and practices of mindfulness, in order to make our mindfulness-based practices more effective and relevant, deriving in part from a perspective of social-emotional learning. Over the past several decades, mindfulness has gained increased attention within the clinical and educational settings, especially as intervention practices. The prevalence of mindfulness-based practice use has tripled between 2012 and 2017 among adults; the prevalence among children aged 4 to 17 years increased 9 times from 2012 to 2017, according to a recent national survey in the U.S. Given such a wide and steady rise in attention, our scientific interest in mindfulness has increased dramatically over the past two decades. However, we still have much work to do to translate appropriate knowledge and skills into effective practice.